Canva-Based Interactive Digital Wayang Multimedia as a Means to Increase Interest and Learning Outcomes in Pancasila Education for Primary School Students - Fani Sri Wulan Dhari; Kurotul Aeni (Universitas Pendidikan Ganesha, 2025)
The low levels of student interest and achievement in socio-cultural diversity material in Pancasila Education present a challenge in elementary schools. This study aims to develop interactive multimedia based on digital wayang using Canva as an innovative learning tool. The method used was Research and Development (R&D), referring to the Borg & Gall model, modified into eight stages. Data collection techniques included observation, interviews, questionnaires, documentation, and pretest-posttest assessments. Expert validation results showed a feasibility score of 89% from the material expert and 90.62% from the media expert, both categorized as “very feasible.” Effectiveness testing revealed an increase in learning interest from an average of 55 to 83.92, and learning outcomes from 56.35 to 82.18. The t-test yielded a significance value of 0.001 (< 0.005), indicating a significant effect of the media on learning outcomes. The developed media is proven feasible and effective, offering an alternative to conventional methods with more engaging and technologically relevant learning experiences.